Bubble or trouble? Restarting professional sports while weighing the risks for athletes - Sidell, M.; Wu, J. (Bryant University, 2020)
During an unprecedented time in our society, professional sports are just starting to make their returns despite not having a vaccine or cure for COVID-19. The NBA is playing in their Orlando bubble in the ESPN World Wide of Sports complex to conclude their season in one place. The NHL has one hub city for each conference, Toronto for the eastern and Edmonton for the western. Looking beyond the two leagues, the impact the pandemic has had on society has been substantial, and restarting sports for the entire country during this time may end up being a tall task. With this, we consider whether or not professional sports and specifically, the NBA and NHL should restart their seasons considering the risks. As the NBA and NHL have just begun their respective restarts, this brings a debate on if these seasons will reach the end and determine a winner.